2019
DOI: 10.1055/s-0039-1678691
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Flaxseed and its Components in the Management of Hypertension

Abstract: This review paper describes the effects of flaxseed and its components (flax oil, secoisolariciresinol diglucoside [SDG], flax lignan complex [FLC], and flaxseed protein hydrolysate [FPH]) on blood pressure (BP) in Sprague Dawley rats (SDR), spontaneously hypertensive rats (SHR), and humans. Flaxseed, flax oil, and FLC had variable effects on BP in humans, while SDG and FPH significantly reduced the BP in SDR and SHR. The effect of SDG was dose-dependent and long lasting. The lowering of BP is mediated through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Studies have confirmed that SDG suppresses dextran sulfate sodium salt-induced colitis [11], serves as an anti-inflammatory and barrier-protective agent in neuroinflammation [12], and exerts antihypercholesterolemic [13] and also angiogenesis and cardioprotection against ischemia-reperfusion injury [14]. In addition, SDG are effective in lowering blood pressure in individuals with hypertension and metabolic syndrome [15] and exert prevention and treatment of arrhythmias and ventricular remodeling postmyocardial infarction [16]. All these studies confirm the role of SDG in inflammation and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 90%
“…Studies have confirmed that SDG suppresses dextran sulfate sodium salt-induced colitis [11], serves as an anti-inflammatory and barrier-protective agent in neuroinflammation [12], and exerts antihypercholesterolemic [13] and also angiogenesis and cardioprotection against ischemia-reperfusion injury [14]. In addition, SDG are effective in lowering blood pressure in individuals with hypertension and metabolic syndrome [15] and exert prevention and treatment of arrhythmias and ventricular remodeling postmyocardial infarction [16]. All these studies confirm the role of SDG in inflammation and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 90%
“…The bioactive found in flaxseed provide these health benefits in many circumstances, and the forms of flaxseed that are necessary to supply these bioactive to the body. Flaxseed from the Linaceae family is a type of herb that has been observed to have significant beneficial effects which mainly include the reduction of blood lipids (Prasad, 2019 ), anti‐diabetic characteristics, hepatoprotective effects, and prevention of many cardiovascular diseases (CVDs) and cancer. The amount of lin plant foods is highest in flaxseeds, which is about 800 times greater than in other plant foods consumed (Patil, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the fatty acid composition in the inner body has also been influenced by this omega-6 and omega-3 fatty acid imbalance in the diet, the incidence of chronic inflammatory diseases could be increased [12]. Various studies have found that omega-3 fatty acids counter the effects of chronic inflammatory diseases associated with cardiovascular diseases [13][14][15], central nervous system diseases [16], diabetes [17], obesity [18] and even several cancers [19][20][21]. Similarly, the omega-6 to omega-3 fatty acid ratio of animal feed is also obviously distorted.…”
Section: Introductionmentioning
confidence: 99%